Utilization of post abortal contraceptive use and associated factors among women who came for abortion service at Debre Berhan Hospital, Debre Berhan, Ethiopia March 2019: Institution based cross sectional study - Muche, Abebe; Bewket, Bekalu; Ayalew, Eferem; Demeke, Endale (Clinical Journal of Obstetrics and Gynecology, 2019)
Background: Post abortion family planning (PAFP) is the initiation and use of family planning methods immediately after, and within 48 hours of an abortion, before fertility returns. In most women fertility returns on average about two weeks after an abortion; however, ovulation can occur as early as 11 days post-abortion. Objective: To assess utilization of post abortal contraceptive use and associated factors among women who came for abortion service at Debre Berhan Referral Hospital, Debre Berhan, Ethiopia March 2019. Methodology: Institutional based cross sectional study design was conducted using hospital data obtained from Gynecology ward in Debre Berhan Referral Hospital, Debre Berhan, Ethiopia, from March 1 -10, 2019. A systematic random sampling technique was used from the abortion register log book. Data was cleaned manually, coded and entered into Epi-data version 3.1 then exported to and analyzed by SPSS version 21 software. Multivariate analysis with AOR, 95% CI and p-value< 0.05 were used to identify variables which have significant association. Result: The finding of the current study showed that among 371 study subjects 170(45.8%) utilized post abortal family planning. There was a significant association between utility of post abortal family planning and post abortion family planning counseling [AOR: 19.245, 95% CI: (10.199, 36.313), p-value= 0.001] and women who were primiparous had 5 times more likely to utilize post abortal family planning as compared to the women who were nullyparous [AOR: 5.314, 95%CI (1.089, 24.210), p value=0.001]. Conclusion and Recommendation: From a total of 371 study subjects 45.8% have utilize contraceptive after abortion service received. This study also showed that parity and counseling’s of family planning were statistically significant associated with utilization of post abortal family planning. We recommend Debre Berhan hospital to scale up activities on post abortal care to increase the number of clients who post abortal family planning.